PENDAMPINGAN DAN PENERAPAN SISTEM PERTANIAN URBAN SEBAGAI MODEL PENGELOLAAN SAMPAH RUMAH TANGGA DI PERUMAHAN BAHRUL ULUM MENARA ASRI JOMBANG - Yuliana, Anggi Indah; Ami, Mucharommah Sartika; Hariono, Tholib (JMM - Jurnal Masyarakat Merdeka, 2020)
The purpose of this service activity is to find out the development of the residents of the Bahrul Ulum Menara Asri Housing in managing household waste as a medium for an environmentally friendly urban farming system. This activity was carried out from August to September 2020 at the Bahrul Ulum Housing Complex, Menara Asri Jombang. This activity used discussion and practice methods. Data collection was carried out through questionnaire sheets to determined the behavior of residents in proper handling of waste and its used as an urban agricultural medium. The evaluation showed that the awareness and behavior of residents in the proper waste sorting and handling activities had increased with this activity. In addition, the participation of residents in processing household waste had also increased. On the other hand, the practice of processing waste into urban farming media increased independence in providing daily food sources, especially the provision of vegetables to meet daily food needed. With this activity, it is hoped that it will contribute to efforts to reduce waste that is wasted to the landfill and increased the independence of residents in managing waste as a medium for an urban farming system so that residents can be independent in provided daily sources of nutrition.